PENGETAHUAN PASANGAN USIA SUBUR TENTANG KANKER SERVIKS - Aisa, Sitti (The Southeast Asian Journal of Midwifery, 2018)
Background: Cervical cancer ranks 2nd in Indonesia that attacks women aged 15-44 years and causes thousands of deaths per year. It is often associated with young age when first having sex and the lack of information obtained affects the knowledge of mothers in fertile couples about cervical cancer. Objective: To determine the relationship of age and information to maternal knowledge about cervical cancer. Method: The analytic study used a cross-sectional design which was conducted at Poasia Health Center of Kendari City, Southeast Sulawesi Province in December 2017. Population was 266 and samples were taken with accidental sampling technique, ie., 57. The data used were primary and secondary data. Data analysis included univariate and bivariate analysis using Chi-Square test. Results: Statistical analysis for age when married with knowledge of cervical cancer showed X2 count (6.92) was greater than X2 table (3,841). For information variable, X2 count (10.07) was also greater than X2 table at 3.841. Thus, there was a relationship between the age at marriage and information obtained by women and knowledge of cervical cancer. Conclusion and Suggestion: Age at marriage and information obtained related to knowledge about cervical cancer. The women are advised to increase knowledge about cervical cancer by following the counseling delivered by health workers to be able to protect themselves from the threat of cervical cancer.